Laying roots in the world: about the dimensions of thinking through Arendt and its meaning for education today (Práxis Educativa, 2018)
This work has a bibliographical character, being based on the analysis of Arendt’s works, and on the interpreters of the author. This paper explores three dimensions of the conception of thinking through Hannah Arendt with the aim of addressing the meaning of education nowadays. The starting point is the distinction between thinking and knowing, and the concept of sensus communis is reconsidered to explore the post-metaphysical and inter-subjective scope of Arendt’s thoughts. In the second step, the Arendtian dimension of thinking as self-examination and its formative character is addressed. Finally, the formative meaning of the dimension of knowing how to be guided by thought is explored. The Arendt-Kant dialogue, following the concept of sensus communis and the maxims of good thinking, shows how the formative dimension identified implies the capacity of putting oneself in the other’s shoes and, consequently, being responsible for one’s own actions, which imposes on education the fundamental ethical demand of taking responsibility towards the world. Keywords: Thinking. Educate. Hannah Arendt.